2020
DOI: 10.1113/jp278362
|View full text |Cite
|
Sign up to set email alerts
|

A novel method using ambient glutamate for the electrophysiological quantification of extrasynaptic NMDA receptor function in acute brain slices

Abstract: Key pointsr We present a novel protocol to quantify extrasynaptic NMDA receptor function utilizing the semi-selective activation of extrasynaptic receptors by ambient extracellular glutamate in acute brain slices from adult rats.r We use whole cell patch clamp to measure the effect of the NMDA receptor antagonist MK-801 on both synaptic and brief, local agonist application-evoked responses.r The level of ambient glutamate was estimated from tonic NMDA receptor activity to be ß77 nM and an equivalent concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 84 publications
(215 reference statements)
4
13
0
Order By: Relevance
“…Next, we confirmed the presence of aberrantly increased basal eNMDAR-mediated currents in MHS cultures by patch-clamp electrophysiological recordings. We found that MHS but not Ctrl hiPSC-neurons manifested basal eNMDAR-mediated current after pharmacological isolation of this current ( 58 ), and NitroSynapsin inhibited the current ( fig. S7E ).…”
Section: Main Textmentioning
confidence: 89%
See 2 more Smart Citations
“…Next, we confirmed the presence of aberrantly increased basal eNMDAR-mediated currents in MHS cultures by patch-clamp electrophysiological recordings. We found that MHS but not Ctrl hiPSC-neurons manifested basal eNMDAR-mediated current after pharmacological isolation of this current ( 58 ), and NitroSynapsin inhibited the current ( fig. S7E ).…”
Section: Main Textmentioning
confidence: 89%
“…Extrasynaptic currents were pharmacologically isolated and measured by whole-cell patch clamp recordings of hiPSC-derived cerebrocortical neurons based on previously published protocols ( 56, 58 ). Briefly, continuous recordings of individual neurons were performed in gap free mode at -70 mV in control conditions, followed by application of bicuculline (50 µM, a GABA A receptor antagonist, Tocris) for 1 min to inhibit inhibitory synaptic inputs and activate synaptic glutamate receptors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, high dose lorazepam may have prevented the neurological manifestation of the disorder from evolving, and third, the patient responded well to the immune globulin treatment. Given the anxiolytic and antidepressant effects of NMDAR antagonists like ketamine, it appears counterintuitive that anti-NMDAR AAbs mediate a depressogenic effect (24). On the other hand, NMDAR activation may lead to opposite effects depending on the subcellular localization and the subunit composition of the receptor (3,25).…”
Section: Discussionmentioning
confidence: 99%
“…Given the anxiolytic and antidepressant effects of NMDAR antagonists like ketamine, it appears counterintuitive that anti-NMDAR AAbs mediate a depressogenic effect ( 24 ). On the other hand, NMDAR activation may lead to opposite effects depending on the subcellular localization and the subunit composition of the receptor ( 3 , 25 ).…”
Section: Discussionmentioning
confidence: 99%